Adaptação, validação e confiabilidade de um teste de agilidade reativa para jogadores de futebol e futsal - Pritsch, Guinter José Klafke (2019)
Soccer and Futsal require the athletes' agility to make fast changes of the body’s direction in response to a stimulus determined by the movements of the ball or the opposing players. However, most agility tests used in soccer players do not include components of reaction to a stimulus. The objectives of this study were to adapt a reactive agility test for field and futsal soccer players based on an existing test for badminton players and to examine the concurrent, construct, and reliability of the results of that test when applied to athletes of these sport modalities. Participants were assessed on two different days, with a seven-day interval. On the first day, the participants performed two agility tests, one test already validated (Agility T Test), but without the cognitive component, and the test developed with a cognitive component, where the participant should move in different directions presented by a visual stimulus (reactive agility test - Futcamp). On the second day, participants performed only the Futcamp. The concurrent and construct validities were verified, respectively, by correlation analysis between the field soccer players' performances in the Futcamp test with the Agility T Test and by Student's t-test for independent measurements comparing the performance of the athletes of different levels or modalities in Futcamp. Finally, to verify possible differences between the two days of the evaluations and the reliability, a comparison was made on the performance of the athletes in the test and retest using Student's t-test for repeated measures and intraclass correlation (ICC) analysis. The performances in the Futcamp and the T Test revealed a low and positive correlation between them. ANOVA showed no difference in time between the groups in the Agility T Test but revealed differences between the groups in the Futcamp test. The ICC values indicated excellent test reliability and field soccer retest. Futcamp was able to identify differences between the modalities (soccer vs. futsal) but was not able to identify differences between the categories in soccer. We can conclude that this study can contribute to the professionals who work with the training of players of these modalities, as it will help in the elaboration and adaptation of different strategies to assist in the training program of field and futsal soccer players.